2022
DOI: 10.1111/sdi.13073
|View full text |Cite
|
Sign up to set email alerts
|

Basic prerequisites for on‐line, high‐volume hemodiafiltration

Abstract: High-volume hemodiafiltration involves filtration of >23 L/treatment and its replacement by sterile non-pyrogenic substitution fluid, while maintaining the patient's fluid balance. That volume of substitution fluid precludes the use of prepackaged sterile fluid. Instead, substitution fluid must be prepared on-line using machines that incorporate a series of bacteria-and endotoxin-retentive filters. The sterilizing ultrafilters are validated to deliver sterile, non-pyrogenic fluid to the patient when operated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…However, some studies have concluded that this dialysis modality is not significantly different from other modalities [ 226 ]. The effects of different dilution modes, dilution ratios and flow rates [ 227 ] during dialysis with OL-HDF on solute clearance [ 228 , 229 ] and dialysate quality [ 230 ] in HF in dialysis patients requires further investigation. Home HD [ 231 ] is a potential therapeutic option with potential benefits in terms of improved LVH, stabilization of blood pressure, increased rates of urinary toxin excretion, improved patient quality of life and reduced medication burden for the patient, which may be associated with a slower ultrafiltration rate and increased frequency of dialysis.…”
Section: Dialysis Treatmentsmentioning
confidence: 99%
“…However, some studies have concluded that this dialysis modality is not significantly different from other modalities [ 226 ]. The effects of different dilution modes, dilution ratios and flow rates [ 227 ] during dialysis with OL-HDF on solute clearance [ 228 , 229 ] and dialysate quality [ 230 ] in HF in dialysis patients requires further investigation. Home HD [ 231 ] is a potential therapeutic option with potential benefits in terms of improved LVH, stabilization of blood pressure, increased rates of urinary toxin excretion, improved patient quality of life and reduced medication burden for the patient, which may be associated with a slower ultrafiltration rate and increased frequency of dialysis.…”
Section: Dialysis Treatmentsmentioning
confidence: 99%